LOCAL ECONOMIC DEVELOPMENT BASED ON VILLAGE POTENTIAL: A LITERATURE REVIEW - Loso Judijanto; Silvia Ekasari; Septina Elida (JOURNAL OF COMMUNITY DEDICATION, 2023)
Village economic development in Indonesia is hampered by the lack of adequate infrastructure and human resources (HR). Improving both is considered essential to facilitate sustainable economic growth at the village level. This research utilises an in-depth literature research method, where data and information are collected from various academic sources, including journals, articles and research reports related to village economic development. The main findings of this study show that infrastructure improvements such as access to proper roads, stable electrification, and internet connection trigger village economic growth by improving the distribution of goods, expanding markets, and increasing efficiency. Meanwhile, empowering human capital through non-formal education and specialised skills training increases productivity and innovation. These investments also show co-benefits, such as improved access to health and education services, as well as strengthening the rural tourism sector. Infrastructure and human capital limitations must be addressed simultaneously to trigger inclusive and sustainable rural economic development. This research confirms that strategic measures, including appropriate investment and empowerment programmes, are important in placing villages on an adequate growth trajectory and harnessing existing local potential into a tangible economic force.